ANALYSIS OF THE BADE WHEELED PHENOMENON IN THE NGABEN CEREMONY STRUCTURE IN BALI - Arya Pageh Wibawa (International Journal of Social Science, 2022)
The purpose of the analysis of the Bade Wheeled Phenomenon in the Ngaben Ceremony Structure in Bali is to reveal the meaning of Wheeled Bade. Bade is known in traditional Balinese culture as an important tool in the Ngaben Ceremony in Bali. However, some Balinese people have replaced the word "bade" with "bade wheels" as a means of Ngaben Ceremony. The problem is centered on: 1) What is the meaning of "bade" in the Ngaben Ceremony?; 2) What is the meaning of "wheeled bade?" The analysis of the Bade Wheeled Phenomenon in the Ngaben Ceremony Structure in Bali has been completed using qualitative methods in the perspective of cultural studies. The technical design of this research is realized based on the non-positivistic paradigm with the help of a semiotic approach. All data was collected through observation and literature study. All data were analyzed in an interpretative qualitative manner using symbol theory and reception theory. The results of the study show that: 1) Ngaben using Bade has a socio-religious meaning for Hindus in Bali. Ngaben is always celebrated using Bade, accompanied by various forms of Hindu sacred ceremonies. Bade has cultural meaning as an instrumental of the pitra yadnya rite that can be useful in fostering kinship in Balinese society; 2) The phenomenon of wheeled bade in the structure of the Ngaben ceremony has added economic value to mediators and users. On the one hand, the wheeled Bade in the structure of the Ngaben Ceremony has reduced the meaning of sacredness and the meaning of solidarity. This happened along with the change in the instrumental meaning of Bade in the Ngaben ceremony.